Social masses and mass societies – similarities and differences - Stanković, Vladan (Sociološki pregled, 2020)
The topic of this scientific work is social masses and the mass society. The subject of research will be reduced to the definition of the notions of “social mass” and “mass society” and finding similarities and differences between them. The author starts from the initial assumption that social masses and mass societies are two similar, but also quite different notions. The following methods were used in the paper: observation, content analysis, developmental method, structural approach, comparative method, analytical approach etc. The scientific justification of the research derives from the establishment of similarities and differences between these two notions, which makes a significant contribution to the construction of the Sociology of the Masses as one of the scientific disciplines of Sociology. The social reach of the research is founded on questioning social masses and the power of the impact of the mass society on contemporary social trends.
Keywords: social mass; mass society; social power; social psychology; culture; politics